2018
DOI: 10.1371/journal.pone.0195455
|View full text |Cite
|
Sign up to set email alerts
|

The experience of discrimination of individuals living with chronic hepatitis B in four provinces of China

Abstract: ObjectivesTo assess chronic hepatitis B (CHB) patients’ knowledge about hepatitis B and their experience of discrimination with regard to study, work, and daily life.MethodsWe administered a questionnaire to 797 CHB patients in four provinces of China and used one-way analysis of variance (ANOVA) and a generalized linear model (GLM) to identify factors associated with discrimination.ResultsCHB patients had low levels of knowledge about hepatitis B. Patients under 40 years of age with a junior college education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 25 publications
6
50
1
1
Order By: Relevance
“…Participants with a higher educational level had better knowledge about HBV transmission than people with a lower education level (e.g., below high school education), suggesting the importance of educating patients living with CHB about HBV and transmission risks. 31 By contrast, our study showed a negative association between anxiety and social environmental QOL and participants with a higher education level (college and above) (Supplemental Table 6).…”
Section: Discussioncontrasting
confidence: 64%
“…Participants with a higher educational level had better knowledge about HBV transmission than people with a lower education level (e.g., below high school education), suggesting the importance of educating patients living with CHB about HBV and transmission risks. 31 By contrast, our study showed a negative association between anxiety and social environmental QOL and participants with a higher education level (college and above) (Supplemental Table 6).…”
Section: Discussioncontrasting
confidence: 64%
“…In addition, previous studies have found that patients with CHB usually suffer stigma/discrimination and are reluctant to disclose that they have the disease. 47 50 Therefore, one-on-one interviews are particularly appropriate in this study to collect disease-related sensitive issues. 51 Demographic and clinical information was collected via a brief questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…For example, almost half of surveyed CHB patients in a Vietnamese study reported feeling discrimination by healthcare workers [69]. Moreover, in a multi-centre study in China, patients with CHB perceived or experienced discrimination in their interactions with medical providers and health staff [78]. Respondents were advised not to have children (4.1% of married respondents), to terminate their pregnancy by medical or family planning department staff (4.8% of female respondents), or refused services for family planning or reproductive health (3.3% and 3.2%, respectively).…”
Section: Stigma and Discrimination By Healthcare Providersmentioning
confidence: 99%
“…There is widespread institutional discrimination encountered by people with HBV that affects multiple aspects of their lives, including their opportunities for education, employment, and residency/citizenship. In a Chinese study, three quarters of people with CHB reported experiencing discrimination because of their hepatitis B infection [78], affecting their education and employment choices and economic opportunities. Indeed, China had enacted laws in the 1980s (which have since been repealed) that limited access to education and employment for people living with CHB [28].…”
Section: Stigma and Discrimination By Institutionsmentioning
confidence: 99%